Pemasangan dan Perbaikan Instalasi PJU sebagai Upaya Peningkatan Penerangan Jalan di Kampung Prapatan Muni Desa Batujajar Kabupaten Bogor - Ramadhan, Marshalin; Sunardi, Sunardi; Supriadi, Oky (Penerbit Widina, Widina Media Utama, 2025)
Inadequate street lighting conditions in rural areas have a direct impact on the safety, security, and comfort of community activities at night. In Batujajar Village, Cigudeg District, Bogor Regency, several road segments remain unpaved and are characterized by dark spots due to damaged or absent Public Street Lighting (PJU). This Community Service Program (PkM) aims to improve the quality of street lighting through the refurbishment and installation of PJU electrical systems, while also enhancing community understanding of PJU operation and maintenance. The implementation method consists of coordination with village authorities and local residents, analysis of existing conditions to determine priority locations, system design in accordance with the General Requirements for Electrical Installations (PUIL), installation and repair of PJU units, and evaluation through field observations and community questionnaires. The program successfully repaired three non-functioning PJU points and installed two new PSL units in areas that previously had no street lighting. All installations utilized standard poles, luminaires, and cables to enhance system reliability and service life. Evaluation results indicate a significant improvement in nighttime illumination levels, as well as increased community awareness regarding PJU operation and maintenance. Based on the questionnaire results, more than 80% of residents reported understanding basic PJU maintenance procedures after the program’s implementation. Overall, this activity generated positive impacts in the form of improved environmental safety, more efficient electricity utilization, and strengthened the role of Universitas Pamulang particularly the Electrical Engineering Study Program in community empowerment through the application of practical, field-based solutions.ABSTRAKKondisi penerangan jalan yang kurang memadai di wilayah pedesaan berdampak langsung pada aspek keselamatan, keamanan, dan kenyamanan aktivitas masyarakat pada malam hari. Di Desa Batujajar, Kecamatan Cigudeg, Kabupaten Bogor, masih terdapat sejumlah ruas jalan belum beraspal dengan titik-titik gelap akibat kerusakan maupun ketiadaan Penerangan Jalan Umum (PJU). Kegiatan Pengabdian kepada Masyarakat (PkM) ini bertujuan untuk meningkatkan kualitas penerangan jalan melalui peremajaan dan pemasangan instalasi listrik PJU sekaligus meningkatkan pemahaman masyarakat terkait pengoperasian dan pemeliharaan PJU. Metode pelaksanaan kegiatan meliputi tahapan koordinasi dengan perangkat desa dan warga, analisis kondisi eksisting untuk penentuan titik prioritas, perancangan sistem instalasi sesuai standar PUIL, implementasi pemasangan dan perbaikan PJU, serta evaluasi melalui observasi lapangan dan kuesioner kepada masyarakat. Implementasi kegiatan berhasil memperbaiki 3 titik PJU yang sebelumnya tidak berfungsi dan memasang 2 titik PJU baru pada area jalan yang belum memiliki penerangan sama sekali. Seluruh instalasi menggunakan tiang, armatur, dan kabel standar guna meningkatkan keandalan dan umur pakai sistem. Hasil evaluasi menunjukkan peningkatan tingkat penerangan yang signifikan pada malam hari serta peningkatan pemahaman masyarakat terhadap operasional dan perawatan PJU. Berdasarkan hasil kuesioner, lebih dari 80% warga menyatakan memahami prosedur dasar pemeliharaan PJU setelah kegiatan berlangsung. Kegiatan ini memberikan dampak positif berupa peningkatan keselamatan lingkungan, efisiensi pemanfaatan listrik, serta penguatan peran perguruan tinggi Universitas Pamulang, khususnya Program Studi Teknik Elektro, dalam pemberdayaan masyarakat berbasis kebutuhan nyata di lapangan.